Perancangan Buku Cerita Bergambar Batu Belah Batu Betangkup - Istiqomah Nadia (IAM Indonesia, 2024)
This design was designed with the aim of introducing the folklore of Batu Belah Batu Betangkup which originates from Indragiri Hilir, Riau. So that in the future more people will know the story of Batu Belah Batu Betangkup. The media used is more effective in packaging. Next, it will be analyzed using SWOT analysis theory. This is done for a creative approach in reaching the target audience so that the goals and messages contained therein can be conveyed well and precisely. Then creating strategic concepts and creative programs really provide solutions in solving problems in design. The design process resulted in the picture book Batu Belah Batu Betangkup. This Picture Story Book is the main media that has interesting visual elements, and a visual story that explains the story of Batu Belah Batu Betangkup. As well as several supporting media such as Posters, Notebooks, Stickers, Pins, X-Banners, T-shirts, Tote bags, Tumblers, Mugs, Lanyards, Study Tables. For this reason, it is hoped that this design can become a medium for education and entertainment, and so that the younger generation and adults can become more familiar with the folklore of Batu Belah Batu Betangkup. Keywords: Design, Picture Story Book, Batu Belah Batu Betangkup